Akkermansia muciniphila Enhances Egg Quality and the Lipid Profile of Egg Yolk by Improving Lipid Metabolism - Wei, Fuxiao; Yang, Xinyue; Zhang, Meihong; Xu, Chang; Hu, Yongfei; Liu, Dan (Frontiers in Microbiology, 2022)
Akkermansia muciniphila (A. muciniphila) has shown potential as a probiotic for the prevention and treatment of non-alcoholic fatty liver disease in both humans and mice. However, relatively little is known about the effects of A. muciniphila on lipid metabolism, productivity, and product quality in laying hens. In this study, we explored whether A. muciniphila supplementation could improve lipid metabolism and egg quality in laying hens and sought to identify the underlying mechanism. In the first experiment, 80 Hy-Line Brown laying hens were divided into four groups, one of which was fed a normal diet (control group), while the other three groups were administered a high-energy, low-protein diet to induce fatty liver hemorrhagic syndrome (FLHS). Among the three FLHS groups, one was treated with phosphate-buffered saline, one with live A. muciniphila, and one with pasteurized A. muciniphila. In the second experiment, 140 Hy-Line Brown laying hens were divided into two groups and respectively fed a basal diet supplemented or not with A. muciniphila lyophilized powder. The results showed that, in laying hens with FLHS, treatment with either live or pasteurized A. muciniphila efficiently decreased body weight, abdominal fat deposition, and lipid content in both serum and the liver; downregulated the mRNA expression of lipid synthesis-related genes and upregulated that of lipid transport-related genes in the liver; promoted the growth of short-chain fatty acids (SCFAs)-producing microorganisms and increased the cecal SCFAs content; and improved the yolk lipid profile. Additionally, the supplementation of lyophilized powder of A. muciniphila to aged laying hens reduced abdominal fat deposition and total cholesterol (TC) levels in both serum and the liver, suppressed the mRNA expression of cholesterol synthesis-related genes in the liver, reduced TC content in the yolk, increased eggshell thickness, and reshaped the composition of the gut microbiota. Collectively, our findings demonstrated that A. muciniphila can modulate lipid metabolism, thereby promoting laying hen health as well as egg quality and nutritive value. Live, pasteurized, and lyophilized A. muciniphila preparations all have the potential for use as additives for improving laying hen production.